An efficient ray‐tracing method for RCS prediction in greco. Issue 3 (28th January 2013) - Liu, Jia; Fang, Ning; Wang, Baofa; Zhang, Lvqian
Abstract Graphical electromagnetic computing (GRECO) is a fast method to predict radar cross section (RCS) of electrically large targets. Combining shooting and bouncing ray method with GRECO is an effective solution for the RCS prediction considering multibouncing effects. However, the ray tracing operation degrades its application due to its computation complexity. In this article, a novel optimization approach based on the binary tree structure is proposed to accelerate the computation process of the proposed algorithm. Numerical results on corner reflectors are used to validate the accuracy and efficiency. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:586–589, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27349